Sustainable architecture - Clokey, Joe; Clokey, Jora; Hammer, Henry; Group Four Teleproductions (Firm); San Luis Video Productions (Los Osos, CA : San Luis Video Publishing, 2004, 1994)
Discusses how and why sustainable building design can save on the use of nonrenewable resources both in the materials and energy used
Title from title screen
Camera, Tom Bartels [et al.] ; music, Russell Autrey
Host: Tom Bartels
Keywords: Architectural design; Architectural